SUPPLY CHAIN MANAGEMENT APPLICATION IN FUNCTIONAL FOOD INDUSTRY - Shegelman, I. R.; Kirilina, V. M.; Vasilev, A. S.; Blazhevich, L. E.; Smirnova, O. E (International Journal of Supply Chain Management, 2020)
Abstract? As follows from the analysis, the producers of functional food production do not increase their production and its supply in the domestic market intensively enough and have a quite low export capacity. During production of functional foods, producers do not pay sufficient attention to patenting of the developed intellectual property objects. It was revealed that Russia, that shows a considerable potential of agricultural land and positive experience of agricultural sector development, needs to ensure the development of domestic supply chain management in businesses and industries to provide promising new-generation functional foods competitive in the internal and external markets. Competitiveness of such products can be improved by development of supply chain management ? specialized functional foods. This paper explores ways of improving supply chain management within the food processing industry looking into characteristics on justification and development of advanced functional food, its formulations and production technologies. This work presents a supply chai nstrategy in terms of food industry subsectors and producers, food effects obtained from functional foods, and in terms of consumers of functional food products depending on product purpose.